Risk factors for recurrent tuberculosis among HIV patients who are on anti-retroviral treatment in rural northeast, South Africa - Kanzoole, Kingsley (University of the Witwatersrand, Johannesburg, 2024)
Background: Tuberculosis (TB) is a major public health concern, and according to the World Health Organization (WHO), is one of the top 10 causes of death worldwide. Recurrent TB is a significant contributor to the overall TB burden worldwide, particularly in areas where TB prevalence is high (4–6), and among HIV infected people. Aim: In this study, we investigated the risk-factors that are associated with the recurrence of TB among HIV infected people in rural northeast, South Africa. Methods: The study employed a retrospective cohort study design and used data from Agincourt health socio-demographic surveillance system spanning from 1st January 2014 to 31st December 2022. Data analysis was conducted using STATA 17 SE as the analytical tool. Cox regression was used to determine risk factors for recurrent TB among HIV patients on ART in rural northeast, South Africa. Results: The study included 4,803 participants with 1,326 (27.6%) males and 3,477 females (72.4%). The participants were predominantly of HIV WHO Stage 1 (84.7%), followed by Stage 2 (7.6%), then Stage 3 (7.0%) and Stage 4 (0.7). The age distribution had 24.8% aged 18-29, 34.5% aged 30-39, 23.1% aged 40-49, 11.0% aged 50-59 and 6.6% aged 60 and above. The study population had a CD4 count median of 229 cells/mm3 with an IQR of 112-390 cells/mm3 and a median duration of previous TB treatment of 31 weeks with an IQR of 16-49 weeks. Out of the 4,803 patients, 396 (8.2%) experienced recurrent TB. This translated to a recurrence rate of 3.0 per 100 person years. The median time to TB recurrence was 1.93 years, with approximately 50% experiencing the recurrence within this period. The significant risk factors associated with recurrent TB were being male (AHR=1.48, CI: 1.11 – 1.96), WHO HIV stage (AHR=2.53, CI: 1.81 – 3.54), baseline CD4 count (AHR=0.98, CI: 0.98 – 0.99), and duration of previous TB treatment (AHR=0.96, CI: 0.93 – 0.98). Conclusion: This study has identified significant risk factors for recurrent TB among HIV patients in rural northeast South Africa. Male patients have a higher risk, necessitating targeted interventions. Advanced HIV stages increase recurrence risk, emphasizing early diagnosis and management. Maintaining higher CD4 counts and continuous monitoring during and after TB treatment are vital to reducing recurrence. These findings inform strategies to improve health outcomes and control recurrent TB among HIV patients receiving ART in the region
A Research Report submitted in partial fulfillment of the requirements for the degree of Master of Science in Epidemiology in the Field of Implementation Sciences to the Faculty of Health Sciences, School of Public Health, University of Witwatersrand, Johannesburg 2024
Keywords: Recurrent tuberculosis; Recurrence rate; ART; HIV; Incidence rate; UCTD; SDG-3: Good health and well-being